The limits of electoral reform - Bowler, Shaun 1958-; Donovan, Todd; European Consortium for Political Research (Oxford Oxford University Press, 2013)
This title examines a variety of reforms, including campaign finance, direct democracy, legislative term limits, and changes to the electoral system itself. This study finds electoral reforms have limited, and in many cases, no effects. The findings here suggest there are hard limits to effects of electoral reform.
Includes bibliographical references and index.
Keywords: Elections; Representative government and representation